FUTSAL ATHLETES' ASSESSMENT: PRESEASON AND SIX MONTHS FOLLOW UP. Issue 7 (11th March 2014) - Bolling, C; Leite, M; Reis, D
Abstract : Background: Futsal has high injury's incidence due to intensive training and reduced recovery time between games. Intrinsic factors, which predispose to injury could be investigated by preseason assessment. Objective: To compare the preseason and 6 months follow up results of single leg hop test and seat and reach test in futsal athletes. Design: This is an observational longitudinal and prospective study to compare preseason results and follow up in different categories futsal athletes. Setting: Athletes from 7 competitive categories under 12, 13, 14, 15, 17, 18, 20 years old and professionals of a Brazilian sports club, competing in national level. Participants: 75 male athletes, mean age of 14.71 years (±2.44), mean weight of 56.95 kg (±12.33) and average height of 166.44 cm (±10.47). Risk factor assessment: The athletes were evaluated using single leg hop test and sit and reach test in February (preseason) and September of 2012. Main outcome measurements: Two tests were analyzed (single leg hop test and seat and reach test) to compare preseason and 6 months follow up results. The paired t-test was used for statistical analysis by SPSS software, version 19.0. Results: All categories except under 17 and 18 showed improvement in values of the single leg hop test (P<.005) on both sides. No significant difference in single leg hop test symmetry were observed except in under 20 (P=.037). The seat and reach test values improved in all categories with a significant difference (P<.005) in under 12, 14 and 15. Conclusions: The changes between preseason and 6 months later were expected and could be associated with improvements in strenght, power and flexibility. The tests changes indicated a physical capacity enhancement revolving around injury prevention by intrinsic factors management.